Evaluation Dietary Sodium and Potassium Effects on Blood Pressure in Women Mirpur AJK (Medical Forum Monthly, 2022)
Objective: The objective of this study to evaluate dietary sodium and potassium effects on blood pressure in women Mirpur AJK.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Department of KIC, Physiology and Biochemistry Mirpur Azad Jammu and Kashmir from January, 2020 to July, 2021 for a period of one and a half year.Materials and Methods: We select 210 women from Mirpur AJK and their blood pressure was assessed both systolic and diastolic pressure. We take history from women and those women take more sodium as compare potassium in their diet placed in Group A and those women take more potassium as compare to sodium in their diet placed Group B.Results: Those women whose take sodium more in their diet their blood pressure was higher that as Systolic BP - 24 hours is (139.9 + 9.2 mmHg) and Diastolic BP - 24 hours is 88.6 + 5.9 mmHg, Those women who take Potassium higher as compare to sodium in their diet, their blood pressure is lower which is Systolic BP - 24 hours 123.4 + 6.3(mmHg) and Diastolic BP - 24 hours 80. 9 + 6.5 mmHg.Conclusion: Sodium salt consumption in diet increased blood pressure with adverse effect in women and potassium salt intake in diet decrease blood pressure in women. There is recommended that women should take potassium containing diet.